Sejarah Perkembangan Ilmu Pengetahuan Di Barat Dan Islam Serta Jenis-Jenis Penalarannya - Fathurrohman, Rizal (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2024)
In fact, the history of scientific progress and expansion is closely intertwined with periodic shifts in the structure of human existence. New findings serve as important building blocks for future discoveries. This causes history to play a big role in the creation of a discovery that is based on historical aspects at that time. However, the history of the evolution of science in the West and Islam is often contradicted, that the history of Western evolution has nothing to do with Islam and vice versa. Here, the researcher wants to explain the history of the evolution of science in the West and Islam and its reasoning. This study uses a library design. This study uses a descriptive analysis method, namely an orderly breakdown of the data that has been obtained, followed by understanding and explanation so that readers can understand it well. Research findings show that the evolution of science in the Western and Islamic worlds has a periodization from each era that is related to each other. 1) Ancient Greek Period (6 BC-6 AD), 2) Middle Ages (6-14 AD), 3) Islamic Period (6-12 AD 4) Renaissance Period (14-17 AD), 5) Modern Era (17 -19 AD), 6) Contemporary Era (20-21 AD). There are three types of scientific reasoning in the West: 1) Deductive (textual), 2) Inductive (contextual), 3) Abductive, while reasoning in the Islamic world there are three types: 1) Bayani (textual), 2) Burhani (contextual), 3) Irfani (intuition).